Buildings as Macro-Cognitive Artefacts: Material Engagement Theory and the Architecture of Thinking-Throughthings―The Case of Moriyama House - Dilaveroğlu, Büşra (Creative Commons, 2026)
This study redefines the ontological status of architecture through the framework of Lambros Malafouris’s Material Engagement Theory (MET). Moving beyond paradigms that treat buildings as passive settings or symbolic forms, it argues that architecture operates as a macro-cognitive artifact―an active, constitutive participant in cognitive life. The investigation centers on Ryue Nishizawa’s Moriyama House, a radically fragmented Tokyo residence that serves as an exemplary “theoretical probe” for tracing the dynamics of material engagement in situ. The analysis is structured around five core MET processes that illuminate the archaeology of cognitive behavior―the layered, historical emergence of thought patterns through material forms: (1) Thinging, or thinking-through-materials; (2) Enactive Signification, where meaning (like “privacy” or “gathering”) is not represented but performed through bodily engagement; (3) Participatory Agency, which co-constitutes action within human-nonhuman intra-actions (4) We-Intentionality, where shared goals materialize through triadic intra-actions among heterogeneous actors; and (5) Metaplasticity, the long-term, reciprocal reshaping of inhabitant habits and architectural wear. Employing a hybrid methodology of architectural analysis and frame-by-frame deconstruction of the ethnographic film Moriyama-San, the research demonstrates how these processes coalesce to form a cognitive habitat.
Keywords: Material Engagement Theory; Cognitive Behavior; Thinging; Enactive Signification; Participatory Agency; We-intentionality; Metaplasticity